2012
DOI: 10.1021/jp211885p
|View full text |Cite
|
Sign up to set email alerts
|

Rate Constant Measurements for the Overall Reaction of OH + 1-Butanol → Products from 900 to 1200 K

Abstract: The rate constant for the overall reaction OH + 1-butanol → products was determined in the temperature range 900 to 1200 K from measurements of OH concentration time histories in reflected shock wave experiments of tert-butyl hydroperoxide (TBHP) as a fast source of OH radicals with 1-butanol in excess. Narrow-linewidth laser absorption was employed for the quantitative OH concentration measurement. A detailed kinetic mechanism was constructed that includes updated rate constants for 1-butanol and TBHP kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 28 publications
9
56
0
Order By: Relevance
“…It is this low temperature region for n-butanol where the biggest discrepancies occurred between the simulated and experimental results. The temperature dependence for the overall reaction rate suggested in [29] is based on a fit to both low temperature measurements below 400 K and the high temperature shock tube measurements of [46] , the uncertainty in the overall rate may be larger in the temperature region of interest here. In addition, a previous global sensitivity study of predicted ignition delays for nbutanol at 725 K and 15 bar [28], demonstrated that the sensitivity to the relative rates of abstractions higher uncertainties for the site specific [29].…”
Section: 2mentioning
confidence: 99%
“…It is this low temperature region for n-butanol where the biggest discrepancies occurred between the simulated and experimental results. The temperature dependence for the overall reaction rate suggested in [29] is based on a fit to both low temperature measurements below 400 K and the high temperature shock tube measurements of [46] , the uncertainty in the overall rate may be larger in the temperature region of interest here. In addition, a previous global sensitivity study of predicted ignition delays for nbutanol at 725 K and 15 bar [28], demonstrated that the sensitivity to the relative rates of abstractions higher uncertainties for the site specific [29].…”
Section: 2mentioning
confidence: 99%
“…Tert-butyl-hydroperoxide (TBHP) was used to produce clean OH rapidly, and has been validated previously for high-temperature studies [32][33][34] 37 as a base mechanism. A submechanism for TBHP decomposition was taken from Pang et al 16 and added to the base mechanism.…”
Section: 1. . . .High-temperature Experiments Of Alkanes + Oh Productsmentioning
confidence: 99%
“…In our optimization scheme, we also imposed the following expected constraint: An optimization problem with Eqs. (12) - (33) and inequalities given by (34) was constructed where the objective function is the error between the measured overall rate constants and calculated overall rate constants using the N-N-N method. Genetic algorithm model was utilized in the calculation and derivation of P, S, and T values.…”
Section: Site-specific Tertiary Abstraction Rate Coefficientsmentioning
confidence: 99%
“…There have been a number of studies of the reactions of OH with the butanols between 250 and 400 K (with a focus on atmospheric chemistry) and several shock tube studies, primarily by the Stanford group, at temperatures of 900-1200 K. [12][13][14][15] OH + CH 3…”
Section: Introductionmentioning
confidence: 99%
“…The shock-tube studies of Pang et al [12][13][14] and Stranic et al 15 were aware of this possibility, that is that measurements simply following the OH decay would be measuring the net rate of OH consumption. In the Pang et al studies, predictions of branching ratios and models of secondary chemistry were used to extract the total rate coefficient and in the study of Stranic et al isotopic labeling of the OH was used to ensure that the total rate coefficient was being measured.…”
Section: Introductionmentioning
confidence: 99%